Computer-Vision-Driven Inspection of Transmission Lines, Towers, and Insulators Using Drone Imagery - Gandhi, Krishna; Verma, Verma (American Journal of Computing and Engineering, 2024)
Purpose: Proper functioning of the power transmission infrastructure is one of the basics of a stable and continuous power supply. Environmental exposure, mechanical strain, and long-term aging are experienced by transmission lines, towers, and insulators on a regular basis, and periodic inspection is a necessity in grid maintenance. Conventional inspection methods, like ground patrols and aerial surveys by helicopters, may be costly, time-intensive, and may be unsafe, and may be challenging to use either at scale or in inaccessible places. Materials and Methods: The increased use of unmanned aerial vehicles (UAVs) has provided the transmission asset with a more versatile and safe option of inspection. High-resolution cameras in drones are able to gather a large amount of visual data at much lower risk of operations and cost of inspection. Nevertheless, when UAV is used at a large scale, it produces high volumes of image data, the examination of which is not feasible and effective manually. Computer vision has emerged as an important tool to use in automation of the process of inspection in order to deal with this challenge. The vision-based techniques allow to detect, locate, and evaluate defects in transmission lines, towers, and insulators based on drone-captured images. This review provides an in-depth analysis of computer-based vision-based methods of inspection of power transmission infrastructure. It talks about UAV platforms and data acquisition plans, image processing and analysis pipelines, classical and learning-based detectors, evaluation plans, and plans of actual implementation. Findings: Summarizing recent literature, the paper pinpoints the existing trends, describes the advantages and the shortcomings of the existing methodology, and unveils the gaps in research to facilitate further development of intelligent systems of inspection of power transmission networks. Unique contribution to Theory, Practice and Policy: Summarizing recent literature, the paper pinpoints the existing trends, describes the advantages and the shortcomings of the existing methodology, and unveils the gaps in research to facilitate further development of intelligent systems of inspection of power transmission networks.